Climbing up and down the hierarchy of accountability: Implications for organization design - Abel G. Romme (Journal of Organization Design, 2019)
The notion of organizational hierarchy is disputed, also in view of the rise of new organizational forms claimed to have "hierarchies without bosses." To better understand the contested nature of hierarchy, this essay provides a systemic perspective on organizational hierarchy defined as a sequence, or ladder, of accountability levels. I then argue this ladder can be used in a top-down manner (e.g., as a chain of command), but also in bottom-up ways (e.g., by employees taking charge of higher-level responsibilities). Subsequently, several propositions that may guide future work in this area are formulated, and the implications for organization design are fleshed out. Overall, the notion of hierarchy may become less contested by defining it as an accountability ladder which can be instantiated and used in highly different ways.
Keywords: 650; Hierarchy; Organization design; Management innovation; Accountability; Authority; Responsibility; Abstraction; Holacracy